(untitled) (Journal of Dhaka National Medical College & Hospital, 2013)
Kidney is the most important vital organ of the body. It is a compound tubular glandular structure which excrete final product of metabolic activity and excess water and ions. It is essential to study the anatomy of renal artery of human kidney in Bangladeshi people with special attention for any variation from standard as well as kidney surgeons for diagnosis and planes of treatment. This is an observational, descriptive type of study carried out in the Department of Anatomy of SSMC from January’2004 to December’2005. The study was performed on 49 pair of human kidney. All these samples were collected from autopsied in the morgue of the Department of Forensic Medicine of Dhaka Medical College and Sir Salimullah Medical College. The collected samples were divided into three age groups, group A (6-20 yrs), group B (21-35 yrs) and group C (37-65 yrs). The present study was done to observe the origin, length and breadth of both renal arteries. Morphological study was carried out by observational and metric method. There was no statistically significant difference found in the origin, length & breadth of the renal arteries in different age groups. The present study will reveal a morphometric baseline data of human renal arteries and compare the data with that of other countries. J. Dhaka National Med. Coll. Hos. 2013; 19 (02): 24-27